Aerodynamic characteristics of a rotating cylinder in the form of a truncated cone - Tanasheva, N.K.; Chirkova, L.V.; Dyusembaeva, A.N.; Sadenova, K.K. (Journal of Engineering Physics and Thermophysics, 2020)
Results of experimental investigations into the aerodynamic characteristics of a rotating cylinder in the form of a truncated cone with a smooth surface and a rough surface have been given. It has been established that the variability of the cross section of the rotating cylinder in an air fl ow in the range of variation in the parameter of conicity 0.25–0.35 ensures a decrease in the drag coeffi cient with the values of the lift coeffi cient being preserved. The results have shown that the presence of the rough surface of the rotating cylinder leads to an increase of 25–30% in the lift. Conditions under which the Magnus effect contributes to the maximum increase in the lift and accordingly the increase in the effi ciency of rotation of the cylinder in the form of a truncated cone have been determined experimentally.
Keywords: rotating cylinder; smooth and rough surfaces; drag; lift; Magnus effect